Developing and maintaining optimal team functioning in curling: a grounded theory study with high performance coaches and athletes - Collins, J. (School of Human Kinetics, Faculty of Health Sciences, University of Ottawa, 2016)
Gaps. Building an effective team and optimizing team functioning in sport is an important, albeit complex and challenging endeavour involving several processes (Bloom, Stevens, & Wickwire, 2003; Collins & Durand-Bush, 2010; Yukelson, 1997). Unfortunately, our knowledge of what constitutes optimal team processes, and how these are developed and maintained within specific sports, remains limited. Although several frameworks targeting a few or several group processes have been put forth in the literature, limitations regarding their theoretical foundation, comprehensiveness, and application have been identified. Collins and Durand-Bush (2015a) made a call for grounded theory research in order to provide an in-depth understanding of team processes required for optimal functioning in specific sports. Given that none of the existing frameworks in the literature have been developed using a grounded theory approach, and none have been tailored to meet the needs of particular sports, this type of inductive research is warranted. Aims. This dissertation had two general aims. The first aim was to critically review theoretical/conceptual frameworks in the literature directly or indirectly addressing team processes in sport and derive implications for professional practice (Article 1). The second aim was to use a grounded theory research approach to investigate (a) factors that contribute to the development and maintenance of optimal team functioning within high performance curling (Article 2), (b) strategies used by high performance coaches and athletes to optimize team functioning (Article 3), and (c) specific roles that curling coaches play in this process (Article 4). Methods. To address the first aim, a critical review of frameworks targeting team processes that were used to guide research and/or practice in sport was performed by first identifying frameworks by searching electronic databases, then doing a content analysis to identify specific team processes that were explicitly reported or could be implicitly inferred based on the literature, conducting a second level of analysis to extract broader team processes, followed by a third level of analysis to identify general themes, and finally comparing specific team processes, broader team processes, and general themes. To address the second aim, a constructivist grounded theory approach (Charmaz, 2006) was used to collect data from 19 high performance curling teams (N = 78 athletes and N = 10 coaches). Of these, seven were men`s teams, 12 were women`s teams, and the 10 coaches were men. Overall, data collection and analysis involved eight steps: (a) conducting interviews (face-to-face focus group interviews with teams of athletes and individual telephone interviews with coaches), (b) transcribing the data (c) reflecting and writing memos, (d) coding the data, (e) performing multiple coder checks, (f) verifying and re-coding the data, (g) developing the grounded theory model, and (h) verifying the model. Results. As indicated in Article 1, seven frameworks used to guide research and/or practice in sport were identified. Three frameworks were borrowed from general psychology while the other four stemmed from the sport psychology literature. On average, the frameworks targeted five general themes (e.g., roles/norms, personal characteristics), six broader team processes (e.g., establish roles, identify team characteristics,) and the outcome of cohesion. The general theme pertaining to roles/norms was the most prevalent one as it was addressed in six out of the seven frameworks. One of the least prevalent general themes related to goals; it was only discussed in two of the seven frameworks. Results show that all of the frameworks were developed using a deductive approach. Article 2 shows that developing and maintaining optimal team functioning in high performance curling is a dynamic process involving numerous factors that influence each other. The Optimal Team Functioning (OTF) model was inductively created to outline key attributes (N=4) and processes (N=17) deemed necessary by high performance curling coaches and athletes for optimal functioning within different contexts. The model comprises eight components under which attributes and processes are grouped: (a) Individual Attributes, (b) Team Attributes, (c) Foundational Process of Communication, (d) Structural Team Processes, (e) Individual Regulation Processes, (f) Team Regulation Processes, (g) Context, and (h) Desired Outcomes. The OTF model is unique because it is comprehensive, sport-specific, inductively derived, and applicable with a strong focus on actions. As seen in Article 3, coaches and athletes reported using many strategies to develop and sustain optimal team functioning. A total of 155 strategies were linked to the eight aforementioned components of the OTF model, which can be targeted when working with teams. Both individual (e.g., journal, apologize for mistakes, do self-assessments) and team strategies (e.g., establish a decision-making process, establish a support team, discuss leadership behaviours) were identified, some of which served multiple purposes (e.g., create a player contract). Unique to the present study was the importance of individual regulation strategies, suggesting that team building interventions should focus on both the team itself and individual members. Communication was involved in most of the strategies, thus methods aimed at enhancing communication within teams should be prioritized. Finally, Article 4 demonstrates that coaches played five major roles in optimizing team functioning: technical/tactical specialist, mediator, facilitator, manager, and motivator. Both coaches and athletes saw value in each of these roles, however, they did not necessarily perceive the importance and characteristics of these roles the same way. Perceptions were dependent on athletes` needs as well as both coaches and athletes` personal characteristics and competencies. In order for coaches to effectively help teams optimize functioning and achieve desired outcomes, specific training should be provided as both coaches and athletes reported that skills and attributes to successfully perform roles were sometimes lacking.